2015
DOI: 10.1093/bjsw/bcv002
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Field Training for the Community: A Student Self-Directed Approach in the Environmental Domain in Jordan

Abstract: This article outlines innovative field training methods that foster the abilities of undergraduate social work students so that they are able to empower the local community and raise awareness of environmental issues. In this study, students were engaged in a local community assessment that sought to understand their views on environmental and community impacts of the Synchrotron-Light for Experimental Science and Applications in the Middle East (SESAME) Project on the lives of the host village's residents. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…On the other hand, a number of studies have shown that social work training has an impact on attitudes towards the natural environment and sustainability (Al-Makhamreh et al, 2016; Boetto and Bell, 2015; Faver and Muñoz, 2013; Jung, 2016; Miller and Hayward, 2014). Thus, it can be concluded that a significant portion of the participants in the current study who were found to ignore sustainability and the natural environment was due to the lack of theoretical courses at postgraduate level on the natural environment and sustainable development.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a number of studies have shown that social work training has an impact on attitudes towards the natural environment and sustainability (Al-Makhamreh et al, 2016; Boetto and Bell, 2015; Faver and Muñoz, 2013; Jung, 2016; Miller and Hayward, 2014). Thus, it can be concluded that a significant portion of the participants in the current study who were found to ignore sustainability and the natural environment was due to the lack of theoretical courses at postgraduate level on the natural environment and sustainable development.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we described a student-initiated field education project with the goal of responding to increasing social isolation and loneliness during the pandemic. The article seeks to contribute to the body of literature on action learning projects for social work field education, a model that has previously been demonstrated in, among other places, Australia (Crisp & Hosken, 2016), Finland (Piippo et al, 2013), India (Panwar et al, 2014), Jordan, (Al-Makhamreh et al, 2016), and Italy (Raineri & Sala, 2019). While consistent with these prior action learning projects, GiftsofGab.org shows how this model can be applicable in a crisis setting in which students were displaced from their field placements and community needs increased in severity.…”
Section: Conclusion and Reflectionmentioning
confidence: 99%
“…Perhaps one of the signs that most clearly indicate the importance of environmental issues in social work is the evident relevance in the literature assumed by the training of the professionals. There is an increasing convergence in affirming that the need for 'greening' social work practice claims for an education transformation integrating environmental content in social work curricula [38], including the field training [39,40] in order to allow future practitioners to address sustainability and social justice promotion in their communitarian intervention [41].…”
Section: Social Work and Environmentmentioning
confidence: 99%